Pengaruh Pendidikan Kesehatan Reproduksi Dengan Metode Stratagem Terhadap Pengetahuan Remaja Putri Tentang Kebersihan Alat Genitalia di SMA Negeri 6 Halmahera Utara - Didide, Christa; Rompas, Sefti S. J.; Kundre, Rina M. (Mapalus Nursing Science Journal, 2023)
Background: Reproductive health education using the stratagem method is an innovation in conveying equality messages in an effort to increase knowledge. The purpose of this study was to determine the effect of reproductive health education with the stratagem method on the knowledge of adolescent girls about genital hygiene. This research method uses an experimental research design, with The One Group Pretest Posttest approach which is tested using the Wilcoxon Sign Rank Test statistical test. The sampling technique in this study used Stratified Random Sampling, and to determine the sample size using the Slovin formula, and obtained a sample size of 84 respondents. The instrument used was a questionnaire with 15 questions. The results showed a significant value of p = 0.000 or a significant value <0.05. Discussion: Before being given health education with the stratagem method, many respondents were in the poor category due to the lack of information obtained by female students about genital hygiene and there was a significant change in knowledge level due to reproductive health education with the stratagem method. The conclusion of this study is that there is an effect of reproductive health education with the stratagem method on the knowledge of adolescent girls about genital hygiene at SMA Negeri 6 North Halmahera Keywords: Adolescent, Genital hygiene, Reproductive health, Stratagem method